Occurrence and characterization of plasmids carrying tmexCD1-toprJ1, blaDHA-1, and blaCTX-M-127, in clinical Klebsiella pneumoniae strains - Qu, Ying; Wang, Wenji; Lu, Qinhong; Qiu, Jihai; Wang, Dongguo; Ma, Liman (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Today, the emergence of Klebsiella pneumoniae with the tmexCD1-toprJ1 gene cassette in patients has presented a significant clinical challenge. Methods To present the detailed genetic features of the tmexCD1-toprJ1 gene cassette of K. pneumoniae strain F4_plasmid pA, the whole bacterial genome was sequenced by Illumina and nanopore platforms, and mobile genetic elements related to antibiotic resistance genes were analyzed with a series of bioinformatics methods. Results K. pneumoniae strain F4 was determined to be a class A+C beta-lactamase, and was resistant to routinely used antibiotics, especially tigecycline, because of the oqxAB gene localized on the F4_chromosome and tmexCD1-toprJ1 on F4_plasmid A. After plasmid transfer assays, the F4_plasmid pA or F4_plasmid pB could be recovered with an average conjugation frequencies of 3.42×10-4 or 4.19×10-4. F4_plasmid pA carried tmexCD1-toprJ1 and blaDHA-1 accompanied by genetic intermixing of TnAs1, Tn5393, TnAs3, and In641, while F4_plasmid pB, bearing blaCTX-M-174, had structural overlap of TnAs3 and In641. Conclusions We suggested that plasmids carrying tmexCD1- toprJ1 might be strongly related to IS26-integrated loop intermediates. This study showed that due to the structural evolution of F4 and related strains, their resistances were so strong that effective antibiotics were virtually unavailable, therefore their spread and prevalence should be strictly controlled.